2021
DOI: 10.3390/mi12080935
|View full text |Cite
|
Sign up to set email alerts
|

Directed Assembly of Particles for Additive Manufacturing of Particle-Polymer Composites

Abstract: Particle-polymer dispersions are ubiquitous in additive manufacturing (AM), where they are used as inks to create composite materials with applications to wearable sensors, energy storage materials, and actuation elements. It has been observed that directional alignment of the particle phase in the polymer dispersion can imbue the resulting composite material with enhanced mechanical, electrical, thermal or optical properties. Thus, external field-driven particle alignment during the AM process is one approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 227 publications
(239 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the coil is expected to be used in the biomedical microrobotics field in the future. Although the material used in this study was a composite of zinc oxide powder in a silicone matrix, various functionalities, such as the electrical conductivity and magnetic field response, are expected when other powder materials are used. , …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the coil is expected to be used in the biomedical microrobotics field in the future. Although the material used in this study was a composite of zinc oxide powder in a silicone matrix, various functionalities, such as the electrical conductivity and magnetic field response, are expected when other powder materials are used. , …”
Section: Discussionmentioning
confidence: 99%
“…For example, several authors have suggested that closed-loop control could potentially be used to fabricate metamaterials with dynamically tunable properties. 45,72,121,122…”
Section: Active Manipulation Of the Equilibrium Statementioning
confidence: 99%
“…In recent years, acoustics-actuated microrobots have gained considerable attention due to their promising potential use in diverse fields [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. With the aid of acoustic actuation, many critical tasks can be performed such as targeted drug delivery [ 12 , 13 , 14 ], particle separation [ 15 , 16 , 17 ], mixing [ 18 ], pumping [ 19 , 20 , 21 , 22 ], self-assembly [ 23 , 24 , 25 ], microsurgery [ 26 ], microfluidic operation [ 27 , 28 , 29 ], and chemical analysis [ 30 ].…”
Section: Introductionmentioning
confidence: 99%